Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Nothnagel, Michael; Fan, Guangyao; Guo, Fei; He, Yongfeng; Hou, Yiping; Hu, Shengping; Huang, Jiang; Jiang, Xianhua; Kim, Wook; Kim, Kicheol; Li, Chengtao; Li, Hui; et al. (Human genetics, 2017)
China has repeatedly been the subject of genetic studies to elucidate its prehistoric and historic demography. While some studies reported a genetic distinction between Northern and Southern Han Chinese, others showed a more clinal picture of small differences within China. Here, we investigated the distribution of Y chromosome variation along administrative as well as ethnic divisions in the mainland territory of the People's Republic of China, including 28 administrative regions and 19 recognized Chinese nationalities, to assess the impact of recent demographic processes. To this end, we analyzed 37,994 Y chromosomal 17-marker haplotype profiles from the YHRD database with respect to forensic diversity measures and genetic distance between groups defined by administrative boundaries and ethnic origin. We observed high diversity throughout all Chinese provinces and ethnicities. Some ethnicities, including most prominently Kazakhs and Tibetans, showed significant genetic differentiation from the Han and other groups. However, differences between provinces were, except for those located on the Tibetan plateau, less pronounced. This discrepancy is explicable by the sizeable presence of Han speakers, who showed high genetic homogeneity all across China, in nearly all studied provinces. Furthermore, we observed a continuous genetic North-South gradient in the Han, confirming previous reports of a clinal distribution of Y chromosome variation and being in notable concordance with the previously observed spatial distribution of autosomal variation. Our findings shed light on the demographic changes in China accrued by a fast-growing and increasingly mobile population.